KUASA NARASUMBER BERITA DALAM MEMBANGUN NARASI BERITA KORUPSI DI PERS LOKAL - Kusumaningrum, Herlina (Universitas 17 Agustus 1945 Surabaya, 2019)
AbstractÂ Researchers have the assumption that local press Jawa Pos Radar Madura in the proclamation of the Fuad Amin Imron corruption cases tend to be predominantly controlled by news sources. Therefore, this research tries to do multiplication related anyone news sources chosen; how the relationship between news resources with entwined Fuad Amin; based on the consideration of what are the resources selected news. To discover it to researchers using a series of methods. First, the resource calculation is done in quantity as well as the number of frequencies in the news. Second, do this resource. Third, doing a reading of the news narrative built JPRM. Fourth, do an in-depth interview about the reasons the consideration of the election of the speaker. Research findings show that the neutral and pro dominant speaker is elected as news sources than news sources cons. Value judgment of news, journalists and security factor is the desire to prevent horizontal conflicts became the cornerstone of the election of the news sources. The research also found that the narrative of JPRM is that Fuad Amin's innocence, even he considered meritorious large Bangkalan.Key word: Corruption, News sources, Local press, News narration